دراسة العمر ومعدلات النمو عند سمك الجربيدة Pagellus erythrinus L. 1758 )) في المياه البحرية السورية (مجلة جامعة اللاذقية- سلسلة العلوم البيولوجية, 2019)
حللت بيانات علاقة الطول مع الوزن والعمر ومعدل الوفيات الطبيعي ومعامل الحالة لعينات شهرية من أسماك الجربيدة من مناطق مختلفة في المياه البحرية السورية خلال الفترة 2007/2008.  بلغ الطول الكلي 10.5- 22.4 سم والوزن 26.78–138.25 غ، وبلغت قيمة علاقة الطول بالوزن (a=0.012, b = 3.019) للذكور و (a=0.081, b=3.173)  للإناث، حيث لم تلاحظ أية فروق معنوية للنمو (P>0.05 ) الذي أخذ النمط المتساوي. تكوّن التركيب العمري لسمك الجربيدة المدروس من  4 مجموعات عمرية( I+,II+,III+,IV+).، وبلغ الطول الأعظمي للذكور   L∞= 33.08, cm k=0.18)) والإناث (L∞=31.47Cm, k = 0.20)، ومعدل الوفيات الطبيعي (0.27) للذكور و(0.30) للإناث، ومعامل الحالة(0.20) للإناث و (0.46) للذكور. بينت نتائج الدراسة وجود صيد جائر لهذا النوع في السواحل السورية كما أظهرت وجود تقارب في الحدود القصوى التي يصلها طول السمك في مياهنا الإقليمية مع تلك المسجلة في المياه البحرية المجاورة كالمياه التركية مثلاً. Data of age, growth, mortality and length-weight relationship were analyzed in Pagellus erythrinus caught from Syrian marine waters during the period 2007/2008.  Total length was 10.5 - 22.4 cm and the gutted weight was 26.78 - 138.25 g. The length-weight relationship was determined as (a=0.012, b = 3.019) for males and  (a=0.081, b=3.173) for females, showing no significant difference (P> 0.05) of this isometric growth. Age structure of this species composed of ( 4) age groups( I+,II+,III+,IV+) and the maximum length was (L∞= 22.31,cm k=0.18) for males and  (L∞=31.47Cm, k=0.20) for females.  Natural mortality (M) was 0.27 for males and 0.30 for females. Condition factors 0.20 for females and 0.46 for males. Results revealed an extra exploitation of that this species is overfished in the Syrian waters and showed a similarity of maximal length of this species in Syrian water compared to the adjacent waters.